2014
DOI: 10.1634/theoncologist.2014-0032
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapies in Metastatic Colorectal Cancer: A Systematic Review and Assessment of Currently Available Data

Abstract: Background. Survival of patients with metastatic colorectal cancer (mCRC) has been significantly improved with the introduction of the monoclonal antibodies targeting the vascular endothelial growth factor (VEGF) and the epidermal growth factor receptor (EGFR). Novel molecular-targeted agents such as aflibercept and regorafenib have recently been approved. The aim of this review is to summarize and assess the effects of molecular agents in mCRC based on the available phase II and III trials, pooled analyses, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 76 publications
0
62
0
2
Order By: Relevance
“…For example, it has previously been demonstrated that PIK3CA mutational status does not predict responsiveness to EGFR inhibitors [19,24,[84][85][86]]; however, pathway-level analyses (e.g., encompassing not only PIK3CA itself but also PTEN and other frequently mutated pathway components) are required to truly ascertain the dependency of the efficacy of EGFR-inhibitor-based therapy on the status of the PI3K/AKT/mTOR pathway. Furthermore, conflicting data exist regarding whether or not BRAF mutation predicts a lack of responsiveness to EGFR inhibitors [87]. Of potential relevance is the ongoing Phase II VISNU-2 trial, which is exploring the impact of PIK3CA and BRAF mutational status on PFS and OS in patients receiving first-line cetuximab + FOLFIRI vs bevacizumab + FOLFIRI in patients with KRAS-WT mCRC, as well as analogously designed future trials investigating additional biomarkers [88].…”
Section: Future Perspectivementioning
confidence: 99%
“…For example, it has previously been demonstrated that PIK3CA mutational status does not predict responsiveness to EGFR inhibitors [19,24,[84][85][86]]; however, pathway-level analyses (e.g., encompassing not only PIK3CA itself but also PTEN and other frequently mutated pathway components) are required to truly ascertain the dependency of the efficacy of EGFR-inhibitor-based therapy on the status of the PI3K/AKT/mTOR pathway. Furthermore, conflicting data exist regarding whether or not BRAF mutation predicts a lack of responsiveness to EGFR inhibitors [87]. Of potential relevance is the ongoing Phase II VISNU-2 trial, which is exploring the impact of PIK3CA and BRAF mutational status on PFS and OS in patients receiving first-line cetuximab + FOLFIRI vs bevacizumab + FOLFIRI in patients with KRAS-WT mCRC, as well as analogously designed future trials investigating additional biomarkers [88].…”
Section: Future Perspectivementioning
confidence: 99%
“…The physical, psychological, and social costs of treatment are onerous for patients with advanced cancer, and the financial costs are particularly high; chemotherapeutic regimens frequently enter the market that are several times more expensive than similarly efficacious medicines [7]. Unfortunately, few comparative effectiveness studies exist in oncology [8], and expensive medications that provide little value over cheaper ones are depleting the financial resources of many Americans [9].…”
Section: High-value Palliative Care Interventions For Patients With Cmentioning
confidence: 99%
“…To a large extent, this progress has been due to molecular targeted therapies which were first introduced in 2004. The concept and implementation of tumor growth inhibition with anti-angiogenic bevacizumab or inhibition of epidermal growth factor receptor (EGFR) signaling with cetuximab and panitumumab has substantially prolonged survival in mCRC compared to traditional chemotherapies alone [1,2,3]. With the recent approval of regorafenib (Stivarga®, Bayer HealthCare, Leverkusen, Germany), the range of treatment options for mCRC after failure of standard therapies in the first and second line has been broadened with a tyrosine kinase inhibitor (TKI) for the first time [4,5].…”
Section: Introductionmentioning
confidence: 99%